DESA MAINU TENGAH KECAMATAN DOLOK MERAWAN KABUPATEN SERDANG BEDAGAI SEBAGI BAGIAN DARI PENGEMBANGAN KOMPETENSI MAHASISWA - Fatimah Zahra Hsb; Sarah Nabillah; Pinky Akalia; Fatma Dewi; Safrida Napitulu (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
KKN stands for Real Work Lecture, which means it is a program activity for students in dedicating themselves to the community which is carried out with an approach starting from the field of social sciences, and others. The KKN that we carried out was from Nusantara Muslim University Al Washliyah Medan which got a location in Central Mainu Village, Dolok Merawan District, Serdang Bedagai Regency. The KKN activities last for 21 days starting on July 10 2023 to July 29 2023. The KKN activities that we will carry out are expected to be a window of enhancing knowledge for students in Central Mainu Village and in the future what we have provided can be useful for all of them in facing the world of education in the future